Evaluation of the efficacy of a double-layered and single-layered synthetic scaffold for the treatment of knee osteochondral defects - an experimental study - Bilge Kagan Yilmaz; Sadik Kaga; Elif Kaga; Hasan Huseyin Demirel; Mehmet Nuri Konya (Journal of Orthopaedic Surgery and Research)
Abstract Background Osteochondral defect (OCD) regeneration is difficult due to the different properties and repair potentials of bone and cartilage tissues. This study aimed to compare cartilage tissue healing by applying in vitro produced double-layered and single-layered scaffolds to osteochondral defects. Methods Ninety male Wester Albino rats with an age of over twelve weeks and a weight of 300–350 g were included in study. Group A was the control group (isolated OCD), Group B received a cellular double-layered scaffold, Group C received a cell-free double-layered scaffold, Group D received a cellular single-layered scaffold, and Group E received a cell-free single-layered scaffold. Biodegradable double-layered and single-layered scaffolds were obtained using L-lactide-co-glycolide (PLGA) and hydroxyapatite (HA) in the bone layer, PLGA and polyethylene glycol methyl ether methacrylate (PEGMEMA) in the cartilage layer. The resulting tissues were stained with Hematoxylin-Eosin and Masson’s Tricrom. Improvement was evaluated at week 4, week 8, and week 12 according to the Modified Mankin and O’Driscol scales. Results The positive impact of scaffold-based cellular applications on morphological field changes was demonstrated. Groups B and C exhibited higher morphological field scores compared to groups D and E. In both scoring systems, group E showed a significant long-term increase. Although the vitality of chondrocyte cells in the scaffolds was confirmed, their desired effects diminished over time. The lowest cell population scores were observed in groups B and D. Although chondrocyte cells demonstrated sustained viability in the double-layered scaffold during the early period, this effect was not observed in the mid and late periods. Conclusions The double-layered scaffold had a limited effect in enhancing osteochondral regeneration. The single-layered scaffold was more effective in enhancing regeneration in the late period. Given the favorable late period outcomes associated with the single-layered scaffold, we propose that further clinical and laboratory studies focus on its long-term results.